Treatment with Oral Ondansetron for Ultramarathon-Associated Nausea: The TOO FUN Study - Andrew V. Pasternak; David Fiore; Arthur Islas; Sarah Toti; Martin D. Hoffman (Sports, 2021)
Nausea and vomiting are common for runners during ultramarathons and often contribute to non-finishes. We aimed to determine the efficacy of ondansetron, a commonly used antiemetic, to treat nausea and vomiting in runners during an ultramarathon. Runners who had a previous history of frequent nausea or vomiting during races and entered in 160, 80, and 55 km ultramarathons in 2018 and 2019 were randomized in a double-blind fashion to 4 mg ondansetron or placebo capsules to use if they developed nausea or vomiting during the race with the ability to take three additional doses. Study participants completed a post-race online survey to assess medication use and efficacy. Of 62 study participants, 31 took either ondansetron (20) or placebo (11). In this small study, there were no group differences in those reporting any improvement in nausea and vomiting (p = 0.26) or in the amount of improvement (p = 0.15). We found no evidence that ondansetron capsules improve nausea and vomiting during ultramarathons.